Mengapa Pemerintah Daerah Belum Berhasil Menerbitkan Obligasi Daerah - Arima Khurria (Syntax Corporation Indonesia, 2023)
Regional bonds are an alternative to infrastructure development financing that needs to be utilized by regional governments. Even though there are still pros and cons regarding regional bonds, regional bonds are still seen as a good and rational financing option. However, until now, no Regional Government has issued regional bonds. The factors that hinder the issuance of regional bonds in Indonesia include obstacles to the readiness of local governments (constraints on the readiness of human resources, the absence of a regional bond management unit, and the absence of regional regulations), regulatory constraints (fragmented regulations, procedures for issuing regional bonds complicated regulations and complex regional bond issuance requirements), political constraints (the existence of an in-principle permit from the DPRD and limited terms of office for Regional Heads and DPRDs), transparency constraints, negative perceptions of debt, local government reluctance to take on debt, and a lack of understanding about bonds area. To overcome these various obstacles, the following factors can encourage the issuance of regional bonds, as encouraging the issuance of regional bonds, including increasing the capacity of local government human resources, improving regulations (a comprehensive regulatory framework), and simplifying issuance procedures and requirements for regional bonds), disclosure, and provision of support by the central government.